KONFLIK SOSIAL DALAM PENGEMBANGAN OBJEK WISATA CANDI MUARA TAKUS DI DESA MUARA TAKUS KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Abdul Jalil; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at Muara Takus Village, district of XIII KotoKampar. This research aims to know any conflict actors in the development of thetourism attractions and causes of the conflict. This research entitled “SocialConflict in the Development of Tourism Attractions of Muara Takus Temple atMuara Takus Village District of XIII Koto Kampar, Kampar District”. The mainissue in this research is what are the factors in causing the conflict in thedevelopment of tourism attractions of muara takus temple and any actors involvedin it. Subjects in this research are: Kampar District Government (Department ofTourism, Youth, and Sport of Kampar District), The BPN office of Kampar(National Land Agency), The PLTA office of Koto Panjang, The District office ofXIII Koto Kampar, The Village Head, People who own land in the area of tourismattractions of muara takus temple, Traditional Leaders, and People who receiveland compensation. The sample in this research is in taken by Random Technique,with the number of subject research as 50 people.The method used was a qualitative descriptive method with qualitative dataanalysis. Data filtering instruments used are observation and interviews.Generally, through the result obtained from this research the researcherconclude: the conflicts in the development of tourism attractions of muara takustemple are vertical and horizontal conflict, between local ellites, instancy togovernment agency, the differences in mission development, while the verticalconflict between the community and government. Conflict factors in thedevelopment of tourism attractions of muara takus temple: From the research thatthe problem of social conflict in the development of muara takus temple is due toland compensation issue which is still floating and is caused by unclear landownership.Kata Kunci : Konflik Sosial, Candi Muara Takus, Kecamatan XIII Koto Kampar